Analysis of the determinants influencing the choice of local market garden crops: tomato, chili, onion, krinkrin and okra in Southern Benin - Adjobo, Olouhitin Mouléro Franck Ronald (European Scientific Journal, ESJ, 2025)
For more than two decades, Benin has witnessed a steady increase in market gardening production. However, his growth has not led to self-sufficiency, as the country still relies on imports from neighboring countries during lean periods. Analyzing the choice of local market garden crops will undoubtedly help find solutions to address the problem. Thus, the study used a multivariate probit model to identify the determinants of the adoption of market garden crops, particularly tomato, pepper, onions, krinkrin and okra, on farms in southern Benin. It was conducted on a sample of 474 randomly selected market gardeners. The results revealed the existence of interdependence and complementarity in the adoption of the various local market garden crops studied. Also, it is observed that the majority of producers surveyed prefer to adopt a combination of two crops at a time (27.43%) or four crops at a time (25.74%). Furthermore, the existence of a market in the village, the level of education, the existence of a telephone network, the type of area in relation to the proximity or not of the water table and the security of the sites are the main factors determining the adoption of local market gardening crops by producers in southern Benin.